VALIDITAS DAN RELIABILTAS ANGKET KEMANDIRIAN BELAJAR SISWA SMP - Yesi Rahmawati; Ecep Supriatna; Wiwin Yuliani (IKIP Siliwangi, 2022)
Independence in learning is student learning activities that are carried out individually without depending on the people around them, initiative, have the desire and awareness and can be responsible for completing assignments and learning problems on their own. Seeing the importance of independent learning for the future of students, an instrument is needed for independent learning. This study has the aim of testing the validity and reliability of the student learning independence questionnaire. The data collection instrument used was a questionnaire consisting of 30 statements with a subject of 60 students of SMP Negeri'2 Batujajar. It is known that from 30 statements, 28 statements were declared valid with a reliability result of 0.830 belonging to the high category. So it can be concluded that this questionnaire is valid and reliable to be used as an instrument to measure student learning independence.Keywords: : Learning Independence, Validity, Reliability